Nanophenomena at surfaces fundamentals of exotic condensed matter properties - Michailov, Michail; SpringerLink (Online service). (Berlin New York Springer, 2011)
This book presents the state of the art in nanoscale surface physics. It outlines contemporary trends in the field covering a wide range of topical areas: atomic structure of surfaces and interfaces, molecular films and polymer adsorption, biologically inspired nanophysics, surface design and pattern formation, and computer modeling of interfacial phenomena. Bridging "classical" and "nano" concepts, the present volume brings attention to the physical background of exotic condensed-matter properties. The book is devoted to Iwan Stranski and Rostislaw Kaischew, remarkable scientists, who played a crucial role in setting up the theoretical fundamentals of nucleation and crystal growth phenomena in the last century.
1. Confined Crystals on Substrates: Order and Fluctuations between One and Two Dimensions.- 2. Multi-site Interactions in Lattice-Gas Models.- 3. Wetting Layer Super-diffusive Motion and QSE Growth in Pb/Si.- 4. Quantum Size Effects in the Growth and Properties of Ultrathin Metal Films, Alloys, and Related Low-Dimensional Structures.- 5. Surface Electromigration and Current Crowding.- 6. Surface-confined Atomic Intermixing at Epitaxial Interface -- 7. Biologically Inspired Surface Physics: The HP Protein Model -- 8. Polymer Chains Adsorption -- 9. Metallic Nano-wires on the Atomic Scale: Correlation between Structure, Electronic Properties and Electronic Transport -- 10. Formation and Opto-Electronic Properties of Nanostructures on Ultrathin SiO2 Covered Si Surfaces -- 11. Step Bunching on Silicon Surfaces under Electromigration -- 12. Step Bunching Instabilities of Vicinal Surfaces during Growth and Sublimation of Crystals: the Role of Electromigration of Adatoms.
Electronic reproduction.
Keywords: Surfaces (Physics).; Crystal growth; Condensed matter; Electronic books